Cultural engagement predicts changes in cognitive function in older adults over a 10 year period: findings from the English Longitudinal Study of Ageing - Daisy Fancourt (Nature Portfolio, 2018)
Abstract There is increasing evidence that leading an active, socially engaged lifestyle might protect against cognitive decline. The arts have been proposed as potentially beneficial activities due to their combination of cognitive complexity and mental creativity. Yet it remains uncertain which types of arts engagement and what level of engagement is required for potential benefits to accrue. This study therefore explored the association between three types of cultural engagement (visiting museums/galleries/exhibitions, going to the theatre/concert/opera and going to the cinema) and change in cognitive function over 10 years amongst adults aged over 52. Our participants (n = 3,445), drawn from the English Longitudinal Study of Ageing, were assessed in 2004/5 and 2014/15. We measured memory and semantic fluency at baseline and follow-up, analysing results using ordinary least squares regression models. Independent of demographic, health and social confounders, visiting museums/galleries/exhibitions and going to the theatre/concert/opera were associated with a lesser decline in cognitive function. Sensitivity analyses confirmed effects were unaffected by considerations of mobility or dementia diagnoses. However, going to the cinema was found to hold little effect for cognitive preservation. Overall, our results suggest that more frequent cultural engagement is associated with more marked effects, but even annual engagement may be protective.